Both organic fertilizer and biochar applications enhanced soil nutrition but inhibited cyanobacterial community in paddy soils - Zou, Xiangbo; Jiang, Xinyu; Guan, Jinshun; Huang, Shaoqiang; Chen, Chuangting; Zhou, Tiancheng; Kuang, Cao; Ye, Ji; Liu, Tong; Cheng, Jiong; Chen, Sanxiong; Yu, Shiqin (Frontiers in Environmental Science, 2024)
Cyanobacteria plays an important role in other ecological processes in paddy soils, particularly in terms of nitrogen input to the ecosystem. Organic fertilizer and biochar are common soil amendment materials used to preserve soil health in agricultural intensification background. However, the consequent increase in soil nutrition may inhibit soil cyanobacteria, therefore decreasing nitrogen fixation and changes other soil processes. To test this hypothesis, we established a 2 × 2 full factorial experiment in a paddy field in South China, which included four treatments: Ctr (control, receiving no organic fertilization or biochar addition), +OF (organic fertilizer application only), +BC (biochar application only), and +Mix (organic fertilizer and biochar applications). The soil cyanobacterial community was analyzed using metagenomics technology, and 14 soil property variables were measured. The results suggested that organic fertilizer was effective in enhancing nutrient levels, leading to a significant increase in extractable and soluble nitrogen, phosphorus, and potassium. In contrast, biochar application had a stronger effect on total soil carbon, potassium, and soil pH. However, both organic fertilizer and biochar applications induced significant decreases in overall cyanobacterial abundance and species number. Dominant cyanobacterial organisms, particularly the two most abundant genera, Leptolyngbya and Phormidium, experienced a greater decrease compared to others. Canonical correlation analyses and structural equation models indicated that organic fertilizer and biochar applications affected soil cyanobacterial community mainly through soil available nitrogen and pH. In total, the present study highlighted that both organic fertilizer and biochar applications in paddy soils notably change soil physicochemical traits, inhibiting rather than benefiting cyanobacterial microorganisms, especially the dominant ones, and potentially reducing nitrogen input. Our study reveals the impacts of oragnic fertilizer and biochar applications in paddies on soil cyanobacteria and how the consequent changes in soil properties mediate this impact, thereby enhancing our understanding of the responses of different soil microbial groups to soil improvement measures.